2017
DOI: 10.1186/s12991-017-0139-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes towards electroconvulsive therapy (ECT) among psychiatrists and family physicians in Saudi Arabia

Abstract: ObjectivesTo assess the knowledge of and attitudes towards ECT among psychiatrists and family physicians in Saudi Arabia.MethodsThe study is quantitative observational cross-sectional with a convenient sample that included psychiatrists and family physicians (including residents) in Saudi Arabia.ResultsOf the 434 questionnaires emailed, a total of 126 returned completed questionnaires (29% response rate). The mean age of respondents was 35 years old. Psychiatrists accounted for 68.3%. The majority were Saudis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…As Beijing Anding Hospital mainly serves patients with acute and severe psychiatric disorders, many patients with major depression have psychotic symptoms, which justified the high percentage of antipsychotic use in this study. The mean number of ECT sessions was 6.7 AE 2.3, which was in the lower range of the usual recommended number of sessions (6)(7)(8)(9)(10)(11)(12) in treatment guidelines in China. 24 One reason for the low number of treatments may be the poor general health of older patients, which reduces their ability to tolerate many ECT sessions.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As Beijing Anding Hospital mainly serves patients with acute and severe psychiatric disorders, many patients with major depression have psychotic symptoms, which justified the high percentage of antipsychotic use in this study. The mean number of ECT sessions was 6.7 AE 2.3, which was in the lower range of the usual recommended number of sessions (6)(7)(8)(9)(10)(11)(12) in treatment guidelines in China. 24 One reason for the low number of treatments may be the poor general health of older patients, which reduces their ability to tolerate many ECT sessions.…”
Section: Discussionmentioning
confidence: 73%
“…8,9 Misconceptions and negative attitudes towards ECT due to its inaccurate portrayal in mass media, irrational fears of electricity, and excessive fear of memory loss have often created controversy around ECT. 8,10,11 However, studies in past decades have reassuringly found that the attitude of patients and their relatives towards ECT are usually positive. [12][13][14][15] Although ECT is often used in older patients, their attitudes and knowledge regarding ECT have not been well studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that negative attitudes toward ECT were common and that respondents who were more knowledgeable about ECT were more likely to consider ECT as a safe and effective treatment option. Several other studies have examined levels of knowledge and attitudes toward ECT among mental health professionals of the various disciplines . Studies have shown that knowledge of and attitudes toward ECT are amenable to targeted ECT education.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have examined levels of knowledge and attitudes toward ECT among mental health professionals of the various disciplines. 11,12 Studies have shown that knowledge of and attitudes toward ECT are amenable to targeted ECT education. Solomon, Simiyon, and Vedachalam 13 and Pranjkovic, Degmecic, Medic Flajsman, Gazdag, Ungvari, and Kuzman 14 found that students received teaching about were more knowledgeable about and more positive about ECT.…”
Section: Introductionmentioning
confidence: 99%